Intraosseous transfusion of hemoglobin vesicles in the treatment of hemorrhagic shock with collapsed vessels in a rabbit model. Issue 7 (24th June 2020) - Hagisawa, Kohsuke; Kinoshita, Manabu; Saitoh, Daizoh; Morimoto, Yuji; Sakai, Hiromi
Abstract : BACKGROUNDS: Intravenous transfusion sometimes encounters difficulty under prehospital conditions when peripheral vessels are collapsed and inaccessible. We investigated whether the cellular type hemoglobin‐based oxygen carriers (Hemoglobin Vesicles: HbVs) allow intraosseous administration into blood circulation for the resuscitation of rabbits with severe hemorrhagic shock. STUDY DESIGN AND METHODS: New Zealand white rabbits (2.5 kg average) were set in severe hemorrhagic shock [mean arterial pressure (MAP): 21 ± 2 mm Hg, Hb 5.1 ± 0.8 g/dL]. Immediately thereafter, 12 mL/kg of HbVs, 5% human serum albumin (HSA), autologous whole blood (WB), stored red blood cells (RBCs) or 36 mL/kg of Lactated Ringer's (LR) were intraosseously transfused, followed by an additional intraosseous transfusion with 8 mL/kg of HSA (following HbV, HSA or stored RBC transfusion), or WB or 24 mL/kg of LR (following LR transfusion), respectively. RESULTS: Intraosseous transfusion of HbVs increased MAP (48 ± 9 mm Hg) and improved hypohemoglobinemia (7.1 ± 0.6 g/dL) as well as WB or RBC transfusion. In contrast, neither HSA nor LR improved hemodynamics or Hb levels. Seven out of 10 rabbits receiving HbVs survived for 24 hours, while only one out of 10 rabbits receiving LR survived (WB and RBC; 100% survivals, HSA; 30% survival). CONCLUSIONS: Intraosseous infusion of HbVs might be an effective initial treatment to maintain hemodynamics during acute hemorrhagic shock. This approach could be used in emergency situations in which access to peripheral vessels is difficult.